Crystallization kinetics and TCV prediction of coal ash slag under slag tapping conditions in an entrained flow gasifier. (15th July 2020) - Ge, Zefeng; Kong, Lingxue; Bai, Jin; Cao, Xi; Zhao, Huiling; Li, Huaizhu; Bai, Zongqing; Meyer, Bernd; Guhl, Stefan; Li, Wen
Abstract: Slag blockages in the bottom of gasifiers cause unplanned shutdowns and huge losses for syngas utilization downstream of gasification. The sudden viscosity increase by crystal precipitation leads to slag blockage during slag tapping in entrained flow gasifiers. The temperature at which the viscosity abruptly increases is the temperature of critical viscosity (TCV ), which is the strict low limit temperature for slag tapping. A comprehensive investigation of slag crystallization kinetics was performed to illustrate TCV in this work. Five slag samples with three different dominant mineral phases that commonly appear in coal ash slag were selected by thermodynamic calculations. The single hot thermocouple technique (SHTT) was applied to analyze the crystallization kinetics based on Avrami and JMA theory. The kinetic analysis indicated that anorthite showed heterogeneous nucleation and grew with a two-dimensional crystalline pattern. The temperature range for anorthite crystallization was approximately 150 °C. Corundum exhibited heterogeneous nucleation and one-dimensional growth pattern. The maximum crystal ratio was 52% for corundum at the temperature of 98 °C. Mullite showed a low E c value, resulting in a high Ton . Rapid crystallization of mullite was observed at 60 °C due to homogeneous nucleation and two-dimensional crystallization. In this work, TCV was revealed by crystallization kinetics for the first time. The relationship between TCV and the activation energy, maximum crystalline rate, and initial crystallization temperature was built to illustrate the influence of crystallization on TCV . Three equations were used for TCV prediction to guide coal selection and slag tapping in entrained flow gasifiers.